Is Video Laryngoscopy the Optimal Tool for Successful Intubation in a Neonatal Simulation Setting? A Single-Center Experience - Musharaf, Iram; Daspal, Sibasis; Shatzer, John (American Journal of Perinatology Reports, 2020)
Background Endotracheal intubation is a skill required for resuscitation. Due to various reasons, intubation opportunities are decreasing for health care providers.Objective To compare the success rate of video laryngoscopy (VL) and direct laryngoscopy (DL) for interprofessional neonatal intubation skills in a simulated setting.Methods This was a prospective nonrandomized simulation crossover trial. Twenty-six participants were divided into three groups based on their frequency of intubation. Group 1 included pediatric residents; group 2 respiratory therapists and transport nurses; and group 3 neonatal nurse practitioners and physicians working in neonatology. We compared intubation success rate, intubation time, and laryngoscope preference.Results Success rates were 100% for both DL and VL in groups 1 and 2, and 88.9% for DL and 100% for VL in group 3. Median intubation times for DL and VL were 22 seconds (interquartile range [IQR] 14.3–22.8 seconds) and 12.5 seconds (IQR 10.3–38.8 seconds) in group 1 (p = 0.779); 17 seconds (IQR 8–21 seconds) and 12 seconds (IQR 9–16.5 seconds) in group 2 (p = 0.476); and 11 seconds (IQR 7.5–15.5 seconds) and 15 seconds (IQR 11.5–36 seconds) in group 3 (p = 0.024).Conclusion We conclude that novice providers tend to perform better with VL, while more experienced providers perform better with DL. In this era of decreased clinical training opportunities, VL may serve as a useful tool to teach residents and other novice health care providers.
Keywords: direct laryngoscopy; intubation; neonatal; simulation; video laryngoscopy